ROLE OF PRIVATE SECTOR IN OWNERSHIP AND FUNDING OF SECONDARY EDUCATION IN ANAMBRA STATE, NIGERIA - Ikedimma, Ifeanyi Francis; Oshia, Eucharia Chinwe; Dike, Ifeoma Ezinwa (UNIZIK Journal of Educational Management and Policy, 2024)
The study aimed at investigating the role of private sector in ownership and funding of secondary education in Anambra State, Nigeria. The descriptive survey research design was adopted to provide the right blueprint for the study and two research questions were formulated to guide the study. The population of the study comprised all the 686 principals of the 686 private secondary schools in Anambra State, Nigeria. Multi-stage sampling procedure was used to draw 446 principals as the sample for the study. The researchers developed a structured questionnaire titled ‘Private Sector, Ownership and Funding of Secondary Education Scale’ (PSOFSES), and it was used to collect relevant primary data, and was validated by 3 experts. The reliability test of the questionnaire was ascertained through Cronbach Alpha method, and with a coefficient of 0.83 was considered satisfactory for the study. The researcher administered the instrument together with the help of 10 research assistants. Mean was utilized as the descriptive statistical parameter to present and interpret results that answered the research questions. The study found that the role of the private sector in relation to ownership of secondary education among others include: bearing the cost involved in the acquisition of land for setting up of the school, school buses and vehicles for operation, legal registration of the school/business name for operations, and constantly promoting the school’s vision, mission, programmes and activities, as well as bearing the cost of maintenance of the school plants. It was concluded that both schools type enjoy the inherent benefits and bear potential risks, taking responsibility in sourcing for funds, allocation of funds, and utilization of funds to keep the school operational and sustainable